Constitutions as Intergenerational Contracts: Flexible or fixed? - Jörg Tremmel (Intergenerational Justice Review)
Constitutions enshrine the fundamental values of a people and build a framework for a state’s public policy. With regard to intergenerational justice, their endurance gives rise to two concerns: the (forgone) welfare concern and the sovereignty concern. In this paper, I outline a procedure for constitution- amending that is intergenerationally just. In its line of reasoning, the paper debates ideas such as perpetual constitutions, sunset constitutions, constitutional reform commissions and constitutional conventions both  historically and analytically. It arrives at the conclusion that recurrent constitutional reform commissions in fixed time intervals strike the best balance between the necessary rigidity and the necessary flexibility of constitutions.